A 3D‐Printed Microfluidic Sensor Platform for Online Bioprocess Monitoring - Christopher Heuer; Anton Enders; Steffen Winkler; Martin Klaßen; Thorsten Teutenberg; Janina Bahnemann (Advanced Sensor Research)
Abstract In order to screen for optimal bioprocess parameters at higher throughput, researchers developing new biopharmaceuticals are increasingly turning to miniaturized cultivation systems with reduced space and media consumption. However, these systems still face challenges related to the continuous monitoring of critical bioprocess parameters, in particular, because sensor integration is often difficult, and sample volumes for offline measurements are limited. In this work, a novel 3D‐printed microfluidic lab‐on‐a‐chip sensor platform is presented, specifically designed to be compatible with a range of cultivation systems (including shake flasks, bioreactors, and custom microbioreactors). The microfluidic system acts as a miniaturized bypass, integrating sensors for real‐time monitoring of key bioprocess parameters (such as pH, pO₂, pCO₂, glucose, and lactate) without compromising culture volume. This system has been successfully applied in a proof‐of‐concept for the cultivation of Escherichia coli and Saccharomyces cerevisiae. In addition, this platform also includes an integrated sampling unit for small‐volume collection, thereby potentially enabling the analysis of complex analyte mixtures such as amino acids or recombinant proteins. The presented system thus represents a valuable tool for both real‐time online monitoring and offline analysis, contributing to the optimization of biopharmaceutical production processes.